EP 8. Motor outcome of the bilateral subthalamic stimulation in Parkinson's disease, one-year follow-up results from the Neuromodulation Centre in Budapest. Issue 9 (September 2016) - Tamás, G.; Kelemen, A.; Albert, D.; Rózsa, I.; Csibri, E.; Entz, L.; Fabó, D.; Halász, L.; Rudas, G.; Barsi, P.; Golopencza, P.; Eröss, L.
Abstract : Introduction: In collaboration of the Department of Neurology at Semmelweis University, and the National Institute of Clinical Neurosciences, we have performed 59 DBS implantations in movement disorders since 2009. Thirty-four patients have been operated with Parkinson's disease (PD). Objectives: In our Centre, we calculated the overall motor outcome of the bilateral subthalamic DBS therapy in PD during a one-year follow-up. Patients & methods: Twenty-eight patients with Parkinson's disease (18 females, 10 males), who had a follow-up visit one year after the operation, were enrolled to the study. Each patient underwent a bilateral DBS lead and pulse generator implantation simultaneously. For individual anatomical planning, stereotactic contrast-enhanced CT sequences, contrast-enhanced 3D T1 weighted images and T2 weighted MRI (3T) images were merged. The individual anatomical target in the STN was selected according to standard stereotactic principles. Dopaminergic medication was withdrawn 12 h before the operation. Electrophysiological mapping was executed with five microelectrodes; clinical symptoms were controlled through macrostimulation. Lead implantation was carried out using local anesthetics, and was assisted by fluoroscopy, while the implantation of the pulse generator was carried out under general anesthesia. The UPDRS (Unified Parkinson's Disease Rating Scale) total score, the subscores, and the Hoehn–Yahr stage were all measured preoperatively and at a postoperative control for 12–18 months. For statistical analysis, we used the Wilcoxon signed-rank test. Results: At the time of operation, the mean age of the patients was 60 ± 8.8 years (mean ± standard deviation) with the disease duration of 12 ± 5.3 years. Before the operation, the patients had been under levodopa therapy for 9 ± 5.4 years. The levodopa equivalent dose was 1000 ± 480 mg before and 491 ± 329.4 mg after the operation ( p < 0.001). The UPDRS subscores has changed as follows [preoperative/postoperative; median(quartile)]: UPDRS I: 1(2)/1(3) point ( p = 0.34); UPDRS II in OFF state: 18(12)/8(6) points ( p < 0.001); UPDRS II in ON state: 7(8)/6(4) points ( p = 0.06); UPDRS III in OFF state: 35(30)/10(7) points ( p < 0.001; 71.4% improvement); UPDRS III in ON state: 10(10)/7(6) points ( p < 0.001); UPDRS IV 6(5)/1(4) points ( p < 0.001); UPDRS-total scores: 63(42)/21(5) points( p < 0.001). The balance scores (in medication-OFF state): UPDRS II/13 point (falling): 0(1)/ 0(1) points; UPDRS III/29 (postural instability): 2(1)/1(1) points ( p = 0.045). The difference of the pre- and postoperative points in the modified Hoehn–Yahr scale was 1.5(1.5). Conclusion: Similarly to international results, the bilateral subthalamic stimulation has markedly improved the motor function of our patients. Furthermore, the postural instability score has also significantly decreased after the operation.